Analysis of Pragmatic in The Addams Family (2019) Animated Film using Semiotic Theory Approach - Salam, Nurrahma Fadhila; Kusumawardhani, Mega Iranti (Visual Communication Design Department of Universitas Pelita Harapan, 2023)
Depending on the communicator, language can give a wide range of meanings and significance. The Addams Family (2019) is an animation film with a unique communication style for conveying messages and information to the audience. Each of the characters’ conversations has several layers, so the audiences have to interpret the messages from various points of view. The authors try to connect the characters’ conversations from the film with the pragmatic theory to decode the meaning. In addition to pragmatic theory, a semiotic approach to denotative and connotative meanings is also used. Authors utilized both quantitative and qualitative methods to calculate, observe and explore a deeper meaning of language. The result is analyzed Pragmatics from the Addams Family characters as shown in the Addams Family (2019) animated film version.